Imaging Arterial Fibres Using Diffusion Tensor Imaging—Feasibility Study and Preliminary Results. (3rd January 2010) - Flamini Flamini, Vittoria Vittoria; Kerskens Kerskens, Christian Christian; Moerman Moerman, Kevin M. Kevin M.; Simms Simms, Ciaran K. Ciaran K.; Lally Lally, Caitríona Caitríona
Abstract : MR diffusion tensor imaging (DTI) was used to analyze the fibrous structure of aortic tissue. A fresh porcine aorta was imaged at 7T using a spin echo sequence with the following parameters: matrix 128 × 128 pixel; slice thickness 0.5 mm; interslice spacing 0.1 mm; number of slices 16; echo time 20.3 s; field of view 28 mm × 28 mm. Eigenvectors from the diffusion tensor images were calculated for the central image slice and the averaged tensors and the eigenvector corresponding to the largest eigenvalue showed two distinct angles corresponding to near 0 ∘ and 180 ∘ to the transverse plane of the aorta. Fibre tractography within the aortic volume imaged confirmed that fibre angles were oriented helically with lead angles of 15 ± 2.5 ∘ and 175 ± 2.5 ∘ . The findings correspond to current histological and microscopy data on the fibrous structure of aortic tissue, and therefore the eigenvector maps and fibre tractography appear to reflect the alignment of the fibers in the aorta. In view of current efforts to develop noninvasive diagnostic tools for cardiovascular diseases, DTI may offer a technique to assess the structural properties of arterial tissue and hence any changes or degradation in arterial tissue.